Metallic nanoparticles influence the structure and function of the photosynthetic apparatus in plants - Tighe-Neira, Ricardo (Plant physiology and biochemistry : PPB, 2018)
Crown Copyright © 2018. Published by Elsevier Masson SAS. All rights reserved.